Key Statistics and Trends in International Trade 2023 - UN Trade; Development (United Nations, 2024)
Key Statistics and Trends in International Trade is a yearly publication. It is a product of the Trade Analysis Branch, Division on International Trade and Commodities (DITC), UNCTAD secretariat. This publication monitors the trends of international trade in goods and services in the medium term. The series is part of a larger effort by UNCTAD to analyse trade-related issues of particular importance for developing countries.